Real-time implementation of model predictive control for flow control application - Rosli, N.S. (IEEE Computer Society, 2014)
This paper presents real-time implementation of model predictive control (MPC) of flow process application. The poor performance of classical approach occur when the control system does not provide optimal control process behavior in presence of non-linearities. Therefore MPC is highlighted as advanced process control for dynamic model system. A control algorithm is focused on developing MPC using MATLAB/Simulink Toolboxes. The algorithm is applied to a pilot plant to see the performance of the controller which the plant is interfaced to MATLAB/Simulink environment via DAQ data acquisition card. The performance of MPC is compared with classical PID controller based on step response and their robustness in presence of disturbance. Â© 2014 IEEE.